2018
DOI: 10.3390/ijms19103148
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Additive Manufactured Scaffolds Designs for Triple Negative Breast Cancer 3D Cell Culture and Stem-Like Expansion

Abstract: Breast cancer stem cells (BCSCs) are tumor-initiating cells responsible for metastasis and tumor reappearance, but their research is limited by the impossibility to cultivate them in a monolayer culture. Scaffolds are three-dimensional (3D) cell culture systems which avoid problems related with culturing BCSC. However, a standardized scaffold for enhancing a BCSC population is still an open issue. The main aim of this study is to establish a suitable poly (lactic acid) (PLA) scaffold which will produce BCSC en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 49 publications
0
17
0
1
Order By: Relevance
“…[60][61][62][63][64][65] Commonly used materials for constructing scaffolds are bioactive ceramics (hydroxyapatite, bioactive glasses), synthetic polymers (such as polyglycolic and polylactic acids), and natural polymers (including silk, collagen, chitosan-alginate (CA), and hyaluronic acid (HA)). [66][67][68][69] Polonio-Alcalá et al 70 found that polylactic acid (PLA) scaffolds can promote CSC proliferation and enrichment in breast cancer cells. Florczyk and coworkers 71 showed that 3D CA scaffolds promoted enrichment of the CSC population, including the cells of prostate carcinoma, breast cancer, hepatocellular carcinoma (HCC), and glioblastoma cells.…”
Section: Biomaterial-based 3d Csc Culture Modelsmentioning
confidence: 99%
“…[60][61][62][63][64][65] Commonly used materials for constructing scaffolds are bioactive ceramics (hydroxyapatite, bioactive glasses), synthetic polymers (such as polyglycolic and polylactic acids), and natural polymers (including silk, collagen, chitosan-alginate (CA), and hyaluronic acid (HA)). [66][67][68][69] Polonio-Alcalá et al 70 found that polylactic acid (PLA) scaffolds can promote CSC proliferation and enrichment in breast cancer cells. Florczyk and coworkers 71 showed that 3D CA scaffolds promoted enrichment of the CSC population, including the cells of prostate carcinoma, breast cancer, hepatocellular carcinoma (HCC), and glioblastoma cells.…”
Section: Biomaterial-based 3d Csc Culture Modelsmentioning
confidence: 99%
“…Moreover, this technology could offer several significant advances: • Creation of ideal products. Polymers are common in different medical applications such as tissue engineering [2], and the manufacture of surgical planning prototypes [3][4][5][6][7] and scaffolds [8]. Ceramic materials have also been employed in scaffolds [9].…”
mentioning
confidence: 99%
“…Previously, our research group set up the conditions of the ES-scaffolds using polycaprolactone (PCL) to enrich the BCSC population in MDA-MB-231 cells [26,32]. BCSCs are a small subpopulation of cells capable of self-renewal, giving rise to the bulk of the tumour and responsible for relapse due to their chemoresistance [33,34,35].…”
Section: Resultsmentioning
confidence: 99%